2013
DOI: 10.1530/rep-12-0498
|View full text |Cite
|
Sign up to set email alerts
|

Season-induced variation in lipid composition is associated with semen quality in Holstein bulls

Abstract: Season-induced variation in fatty acid and cholesterol composition in bovine semen has been associated with semen quality. Given the specific roles of the various semen compartments (seminal fluids, sperm head, and sperm tail) in fertilization, we hypothesized that environmental-stress-induced alterations in the lipid composition of a specific compartment might impair semen quality and sperm function. Semen samples were collected from five mature Holstein-Friesian bulls during the summer (August to September) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…Martínez-Fresneda et al [84] suggested that the seasonal fluctuations in sperm cryotolerance could be associated with changes in the membrane composition of sperm, occurring during spermatogenesis as a result of variations in the proliferative activity of germ cells and Sertoli cells among seasons. In line with this hypothesis, earlier studies found seasonal changes in the phospholipid, cholesterol and protein content of sperm [85,86]. Moreover, Westfalewicz et al [86] reported that the majority of proteins that underwent changes in abundance during seasons came from seminal plasma.…”
Section: Molecular Mechanisms Involved In Those Factors That May Affementioning
confidence: 76%
“…Martínez-Fresneda et al [84] suggested that the seasonal fluctuations in sperm cryotolerance could be associated with changes in the membrane composition of sperm, occurring during spermatogenesis as a result of variations in the proliferative activity of germ cells and Sertoli cells among seasons. In line with this hypothesis, earlier studies found seasonal changes in the phospholipid, cholesterol and protein content of sperm [85,86]. Moreover, Westfalewicz et al [86] reported that the majority of proteins that underwent changes in abundance during seasons came from seminal plasma.…”
Section: Molecular Mechanisms Involved In Those Factors That May Affementioning
confidence: 76%
“…Valeanu et al (2015) found no significant differences in motility of bull sperms between seasons, while other authors report significantly better characteristics of bull semen in different seasons. Winter season was stated as the best by Argov-Argaman et al (2013);Bhakat et al (2014) and Alragubi (2015), summer season by Sarder (2007) and Snoj et al (2013). Differences can be explained by different climatic conditions in followed studies.…”
Section: Discussionmentioning
confidence: 96%
“…Ball and Peters (2004) reported that sperm characteristics are not affected only by the ambient temperature at the time of semen collection, but also during the sperm maturation in epididymis and during spermatogenesis, namely about 70 days prior the collection. The seasonal variations in semen characteristics have been described in many studies (Graffer et al, 1998;Haugan et al, 2005;Sarder 2007;Argov-Argaman et al, 2013;Snoj et al, 2013;Bhakat et al, 2014) as well as the effect of the month of collection (Pileckas et al, 2013). However, these studies were conducted mostly, except study from Snoj et al (2013) who collect bull semen in central region Slovenia, under tropical and subtropical climates or under daylight conditions differing from those prevailing in Central Europe.…”
Section: Introductionmentioning
confidence: 95%
“…We observed that the predominant fatty acid was DHA, representing 44.9% in spermatozoa and 31.5% in seminal plasma of all the fatty acids. However, in bull, the proportion of DHA is about 30% in spermatozoa and 20% in seminal plasma of the total fatty acids (Argov‐Argaman et al ., ,b). On the other hand, in stallion, the spermatozoa contain high levels of docosapentaenoic acid (DPA), representing on average the 49.9%, followed by palmitic (C16:0) and stearic (C18:0) acids, representing the 17.6% and 8.7% respectively (Macías García et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The spermatozoa of species resistant to cryopreservation (bull, rabbit and human) present higher levels of PUFA and cholesterol than the spermatozoa of more sensitive species (boar and ram) (Watson, ). The sperm fatty acid profile was described in boar and stallion; however, the complete profile (spermatozoa and seminal plasma) was identified only in bull and human (Waterhouse et al ., ; Macías García et al ., ; Argov‐Argaman et al ., ,b; Martínez‐Soto et al ., ). Nevertheless, information about a wide range of fatty acids in the ram semen is still lacking.…”
Section: Introductionmentioning
confidence: 99%